Why cash transfer programs can both stimulate and slow down job finding - Juliana Mesén Vargas; Bruno Van der Linden (IZA Journal of Labor Economics, 2019)
This article analyzes the behavioral effects of cash transfer programs when jobless people need to have access to a minimum consumption level. Our model reconciles recent evidence about negligible or favorable effects of cash transfers on job-finding rates and the more standard view of negative effects. When unemployment compensation, if any, is low enough, we argue that cash transfer programs can raise the hiring probability. Our framework is flexible enough to generate the standard conclusion as well. Looking specifically at unemployment compensation, its optimal level is generally higher than when a lower bound on consumption is ignored.
Keywords: D91; H21; I32; J64; J65; 330; poverty; unemployment; optimal insurance